Household consumption and savings rate depend strongly on employment status, income, and age - Karl Brenke; Jan Pfannkuche (DIW Weekly Report, 2018)
On what and to what extent private households in Germany spend money varies significantly depending on employment status, income, and age. As this study based on the most current official sample survey of income and expenditure from 2013 shows, unemployed households on average spend over half of their income on basic needs such as living and food expenses while unemployed people living alone spend almost two-thirds on basic needs. Employed and retired households with multiple adults, on the other hand, spend only one-third of their income on living and food expenses. Model calculations show that recent price increases of goods and services have affected all households to a similar degree. Before 2013, low-income households were slightly more affected than others due to their consumption patterns. The savings rate also depends on employment status, income, and age. While low-income households even go into debt, many other households are sometimes saving 20 percent or more of their income. On average, every household saved a good 17 percent of their income in 2013.
Keywords: E21; D31; D12; 330; consumer spending; saving rates in Germany